A systematic review on the effectiveness of active recovery interventions on athletic performance of professional-, collegiate-, and competitive-level adult athletes - Ortiz Jr, R. O.; Sinclair Elder, A. J.; Elder, C. L.; Dawes, J. J. (The Journal of Strength and Conditioning Research, 2019)
Active recovery (AR) is a popular approach to enhancing athlete recovery from participation through physical action, and it has a perceived benefit in the recovery of athletes' enhancement of postexertional physiological status; however, it is unclear whether these recovery techniques enhance athletic performance. The purpose of this systematic review was to examine the effects of AR interventions conducted postexertion on athletic performance among professional, collegiate, and competitive adult athletes. Articles were collected via 4 online databases restricted to publication in English between 1998 and 2014. After the evaluation of overlap among the databases and abstract review, 150 potential eligible studies remained. Twenty-six articles involving 471 subjects remained after full analysis. The primary exclusion factor was absence of AR types of interest or measures of performance. The review resulted in a wide variety of findings indicating the vagueness in AR approach and outcome measures, making it difficult to draw specific conclusions. The review demonstrated that AR interventions lasting 6-10 minutes revealed consistently positive effects on performance. The appropriate intensity level of AR sessions was inconclusive in the literature; however, blood lactate clearance rate as a recovery marker appeared unreliable. The review suggests that there are positive psychological outcomes from AR sessions, a need to determine if AR should be individualized in its application, and weak evidence regarding the efficacy of postexercise AR, particularly relating to performance. Future research is needed for reliable and accurate markers for fatigue, physiological recovery, performance, and markers of intensity and duration for AR interventions.